2014
DOI: 10.2147/ijn.s73144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adsorbed and templated nanosilver in mesoporous calcium-silicate nanoparticles on inhibition of bacteria colonization of dentin

Abstract: Mesoporous calcium-silicate nanoparticles (MCSNs) are advanced biomaterials for controlled drug delivery and mineralization induction. Nanosilver-incorporated MCSNs (Ag-MCSNs) were prepared in the present study using both the adsorption and template methods. Both versions of Ag-MCSNs showed characteristic morphology of mesoporous materials and exhibited sustained release of ions over time. In antibacterial testing against planktonic Enterococcus faecalis , Ag-MCSNs showed significantly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…Among the 52 papers, 11 have studied pure BGs, 23 have assessed doped‐glasses, and 18 have used composite materials …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 52 papers, 11 have studied pure BGs, 23 have assessed doped‐glasses, and 18 have used composite materials …”
Section: Resultsmentioning
confidence: 99%
“…Two articles have studied the effect of Ag‐BG on BMSCs. The first has concluded that the way Ag is incorporated determines the toxicity: adsorption being more toxic than templating.…”
Section: Pure Bgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesoporous calcium silicate nanoparticles (MCSNs) are newly synthesized advanced materials with multi-functions for root canal filling because of their special nanostructure, injectability, mineralization of apatite, antibacterial capability and drug delivery [7]. They can release Ca and Si ions and show great ability to deliver various biomolecules in a sustained manner [8][9]. The potential antimicrobial mechanisms of MCSNs are they release SiO 4 4− and Ca 2+ , creating a weak alkaline microenvironment, and the nano-size MCSNs could infiltrate the bacteria [7].…”
mentioning
confidence: 99%
“…The potential antimicrobial mechanisms of MCSNs are they release SiO 4 4− and Ca 2+ , creating a weak alkaline microenvironment, and the nano-size MCSNs could infiltrate the bacteria [7]. They are considered as excellent platforms for the efficient delivery of drugs and osteanagenesis [8][9].…”
mentioning
confidence: 99%